Incorporating the Xper MTB/RIF in the screening of Pulmonary Tuberculosisi in patients admitted to the Emergency Department of a Public Hospital. Lima-Perú - Huaroto, Luz (2024)
Patients with pulmonary tuberculosis (PTB) often present with atypical clinical symptoms in EmergencyDepartments (ED), which hinders early detection. Traditional screening is based on “cough with expectoration ≥ 15 days”, however, some patients produce sputum, without coughing. Consequently, in this study, TB screening was performed through active case finding, regardless of the presence or duration of respiratory symptoms and included the Xpert MTB/RIF test. The study was carried out under field conditions at the Dos de Mayo National Hospital's ED in Lima, Peru from 2017-2018. The study enrolled patients age ≥ 18 years , who could produce sputum, regardless of cough duration. Patients with a current TB diagnosis were excluded. Additional personnel were assigned for obtaining the informed consent, administering questionnaires and collecting sputum samples. Smear, Xpert MTB/RIF and culture with the Ogawa media were performed. Three methods were evaluated: 1) smear 2) Xpert MTB/RIF, 3) the combination of both. Active TB was diagnosed in 35/567 (6.17%) patients. Sensitivity rates were 37.14% for smear microscopy, 68.57% Xpert MTB/RIF, and 74.29% the combined approach. Among 35 PTB patients, 11 were detected by all three methods, 6 only by Xpert MTB/RIF and 9 exclusively through culture, identified several weeks later. Rifampicin resistance was found in 6 of 35 cases. The study concluded that combining smear microscopy with Xpert MTB/RIF in EDs enhances screening sensitivity, facilitates early diagnosis of rifampicin resistance, and reduces the time to diagnosis.